Is the DNA analysis the key to freedom for the wrongfully convicted? - Đurđević, Tijana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The fact that nearly five hundred wrongfully convicted are exonerated thanks to subsequent DNA analysis, after the discovery of the DNA and the possibility of identifying person on a basis of the DNA, inspired us to research the issue of the wrongful convictions globally and the role of the DNA analysis in their correction. The paper first deals with the concept and the consequences, the estimates of the frequency and the causes of wrongful convictions, and then gives an overview of some organizations that deal with cases of wrongful convictions in comparative practice. It further explains the role of the DNA in the exonerations of the wrongfully convicted as well as the assumptions that must exist in order to correct the conviction this way, and very last, it discusses the current possibilities and the prospects in our country regarding the correction of the wrongful convictions through subsequent DNA analysis and in other ways.